Field notes contributed by Raymond L. Cummins, spring 1982 - Cummins, Raymond L.et al (1982)
Field notes were contributed by Raymond L. Cummins and Ronald Harms, observer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed